Effectiveness of Preservation of Kampung Tugu as a Cultural Heritage Area by the Cultural Service of the North Jakarta City Administration - Basir, Siti Nur Laila; Pangestu, Angella Rosha (Universitas Muhammadiyah Ponorogo, 2026)
This study examines the effectiveness of preservation in Kampung Tugu as a Cultural Heritage Area by the North Jakarta City Administration Cultural Sub-Department. The purpose of this study is to determine how the North Jakarta City Administration Cultural Sub-Department strives for the effectiveness of preservation in the Kampung Tugu area which is experiencing degradation. The method used in this study is a qualitative research method by analyzing data using the theory of effectiveness with 5 appropriate indicators, namely Appropriate Policy, Appropriate Implementation, Appropriate Target, Appropriate Environment, and Appropriate Process. This study found that preservation in this area based on Law Number 11 of 2010 concerning Cultural Heritage has not been effective due to degradation in the area and other conflicting policies also apply in the same area, namely the Regulation of the Governor of the Special Capital Region of Jakarta Province Number 31 of 2022 concerning the Detailed Spatial Planning Plan for the Special Capital Region of Jakarta Province. With the findings in this study, it can be used as evaluation material for policy makers and policy implementers in order to determine the status of Kampung Tugu which can then develop this area effectively according to the specified policy. However, this research has not been able to provide the views of policy makers regarding the preservation problems experienced by Kampung Tugu so that further research can add new perspectives from policy makers regarding the problems that occur in Kampung Tugu.